Prenatal Diagnosis of Fetus With Transaldolase Deficiency Identifies Compound Heterozygous Variants: A Case Report - Xue, Jiaxin; Han, Jin; Zhao, Xiaopeng; Zhen, Li; Mei, Shanshan; Hu, Zhiyang; Li, Xiuzhen (Frontiers in Genetics, 2022)
Transaldolase (TALDO) deficiency is a rare autosomal recessive disorder caused by variants in the TALDO1 gene that commonly results in multisystem dysfunction. Herein, we reported compound heterozygous variants in a Chinese prenatal case with TALDO deficiency using whole-exome sequencing (WES) for trios and Sanger sequencing. The heterozygous variants were located on the TALDO1 gene: NM_006755.2:c.574C>T(Chr11:g.763456C>T), a missense variant in exon 5 paternally inherited; NM_006755.2:c.462-2A>G(Chr11:g.763342A>G), a splicing aberration in intron 4 maternally inherited. The qualitative analysis of urinary polyols in neonatal urine indicated that xylitol+arabitol and ribitol in the proband's urine were significantly increased. These findings expand the variation spectrum of the TALDO1 gene, provide solid evidence for the family's counseling in regard to future pregnancies, strongly support the application of WES in prenatal diagnosis, and further prove that effective postpartum treatments could improve prognosis.